The Representation of Earthquakes in Hindu Religion: A Literature Review to Improve Educational Communications in Nepal - Subedi, Shiba; Hetényi, György (Frontiers in Communication, 2021)
In Nepal, after every large earthquake, local people appear to be motivated to get better prepared for future earthquakes. However, their motivation vanishes before effective preparation, mainly due to the lack of earthquake education in their community. Promoting up-to-date scientific knowledge to a society living under high earthquake hazard is important and contributes to reduce the related risk. The dissemination of information in Nepal lags far behind modern seismological knowledge, and part of the local population still believes in religious explanations and stories about earthquakes. We run an educational program in Nepal to make people better aware of earthquakes and to improve their preparedness through obligatory school education, but the dichotomy between scientific and religious visions of earthquakes remains a challenge. For more efficient acceptance of earthquake preparatory advices, it is important to better perceive the religious narration of earthquakes and to include these in the educational communications. Thereby, we reviewed the main sources of Hindu literature and gathered relevant and interesting explanations on earthquake evidences and causes. The primary religious interpretations of earthquakes in different Hindu texts are related to the Gods and their actions, and some sources also include physical descriptions of earthquakes related situations or processes. We found that most of the stories, causes and explanations of earthquake do not match with the concepts of modern science, yet there are exceptions such as a historically old advice to leave buildings during the shaking. The collected findings are important not only from a religious literature review perspective, but also and mainly to develop an inclusive and more efficient strategy to communicate about earthquake related topics in the classroom as well as with the public in Nepal.